Impact of land use and land cover on ecosystem service values in Sekela Woreda, Amhara Region, North-Western Ethiopia - Dagnaw Mekonnen, Addisu (Ecological Questions, 2025)
Land use and land cover are important factors affecting ecosystem services through alteration of the natural environment. The purpose of this study was to assess the impact of changes in land use and land cover (LULC) on ecosystem service values (ESV) in Sekela Woreda. As part of the study, the spatial and temporal dynamics of LULC over the last three decades were analysed. Using ArcGIS 10.6 software, ESVs were obtained for each LULC class. The results of the research show that during the study period, there were changes in land use and land cover in the study area, with agricultural land declining by 4,079.66 ha (–14.98 %) and water bodies by 125.15 ha (–45%), while the area of wasteland, scrubland, woodlands and water bodies increased by 2670.57 ha (7.9%), 363.78 ha (3.87%) and woodlands by 1169.62 (3.22%), respectively. The research has shown that changes in land use and land cover have resulted in a decrease in ESVs of 0.865686 over the last 30 years (1985–2015). Consequently, LULC has had a negative impact on ecosystem services and functions over the past 30 years. Therefore, in order to manage ecosystems in this area in a sustainable manner, it is necessary to protect natural resources and take appropriate intervention measures.